Microchannel interrogation with Twyman-Green Interferometer - Wan Mokhdzani Wan Nor Haimi (School of Microelectronic Engineering, 2011)
The main objective of this study is to develop a non-contact measuring instrument capable of performing depth measurements of a microfluidic channel made of silica wafer.